Clinical value of pediatric sepsis‐induced coagulopathy score in diagnosis of sepsis‐induced coagulopathy and prognosis in children. (22nd September 2021) - Xiang, Long; Ren, Hong; Wang, Ying; Zhang, Jian; Qian, Juan; Li, Biru; An, Kang; Fu, Lijun
Abstract: Background: In adults, sepsis‐induced coagulopathy (SIC) is diagnosed by the SIC score, known as sepsis‐3. There is no pediatric SIC (pSIC) score at present. Objectives: We proposed a pSIC scoring method and evaluated the diagnostic efficacy of the score in the diagnosis of SIC in children. Patients/Methods: Patient data were retrospectively analyzed from Shanghai Children's Medical Center between February 2014 and January 2015. The pSIC score was modified from the SIC score. The area under ROC curve (AU‐ROC) was used to compare the prognostic values of pSIC with other scores for pediatric sepsis‐induced disseminated intravascular coagulation (DIC) to arrive at a 28‐day outcome. Results and Conclusions: There were 54 patients in the pSIC group and 37 in the non‐pSIC group. The Kaplan–Meier survival curve analysis showed that the 28‐day prognosis was better in the non‐pSIC than in the pSIC group ( p  < .001). The AU‐ROC of the pSIC score in predicting 28‐day mortality in sepsis was 0.716, with the optimal cutoff value of >3 inferior to that of pediatric sequential organ failure (0.716 vs. 0.921, p  < .001). The AU‐ROC of pSIC in predicting nonovert DIC was 0.845 and the optimal cutoff value was >3. The AU‐ROC of pSIC in predicting overt DIC was 0.901, with the best optimal cutoff value of >4. The pSIC score can be used to diagnose SIC in children, screen potential nonovert DIC, and assess the severity of sepsis, organ dysfunction, and 28‐day outcome in children.